Emerging Threats: The Latest Cybersecurity Risks and the Role of Artificial Intelligence in Enhancing Cybersecurity Defenses - Jimmy, Fnu (International Journal of Scientific Research and Management (IJSRM), 2021)
In an era marked by the relentless advancement of technology, the realm of cybersecurity confronts a relentless onslaught of increasingly sophisticated threats, presenting formidable challenges to organizations across the globe. Amidst this dynamic landscape, the pivotal role of artificial intelligence (AI) in fortifying cybersecurity defenses has ascended to unprecedented prominence. This research article undertakes a comprehensive examination of the prevailing cybersecurity risks, while also delving into the transformative potential of AI in ameliorating these perilous hazards. Through a meticulous review of extant literature and insightful case studies, the article meticulously delineates emergent cyber threats, elucidating the manifold applications of AI in the realms of threat detection, prevention, and incident response.Furthermore, this research endeavor meticulously elucidates the intricate nexus of challenges and limitations inherent within AI-powered cybersecurity systems, encompassing ethical quandaries and technical impediments. By delineating these complexities, the article endeavors to foster a nuanced understanding of the intricate interplay between AI and cybersecurity. As a culmination of this scholarly discourse, the article proffers cogent insights into prospective trajectories and pragmatic recommendations aimed at harnessing the transformative potential of AI to fortify cybersecurity protocols. This research underscores the imperative for concerted collaboration between policymakers, organizations, and cybersecurity practitioners in navigating the labyrinthine landscape of evolving cyber threats. Through judicious deployment and continual refinement of AI-driven solutions, the collective endeavor to safeguard digital ecosystems against the pernicious machinations of cyber adversaries assumes paramount significance, thereby heralding a new epoch of resilience and vigilance in the realm of cybersecurity.